Equity in suffrage - Edelblute, William H. (My University, 1892)
Introduction: When Adam and Eve were placed in the garden, they were instructed to till it and keep it. Being subjected to the Divine law, they were deprived of their luxurious habitation upon the first betrayal of that trust. From that time on down through the ages, we find men whose only aim is freedom, but whose right to govern and be governed comes from the general good of the whole community. They do not consider even the right to help in the moulding of the power which they are to obey as being a natural right. Men are not born free and equal, consequently the right of suffrage does not stand as the necessary pillar of the social state, but becomes a question of expediency and its practical application demands all the skill of acquired intellect in the judgment of those who exercise it. Their ideas are perfectly natural. A ships crew, having lost its captain, was without a commander. In selecting a proper officer, one would think, they would make their choice from the most experienced, but because all lives were in danger they all had a right to vote. The result was the selection of an inferior seaman and soon the vessel with its logical crew, was a wreck upon the rocks.
Citation: Edelblute, William H. Equity in suffrage. Senior thesis, Kansas State Agricultural College, 1892.
Morse Department of Special Collections
Keywords: Equity; Suffrage; Voting; Majority rule; History; Theses; Manuscripts (documents)